The relationship between in-hospital location and outcomes of care in patients diagnosed with dementia and/or delirium diagnoses: analysis of patient journey. Issue 1 (December 2016) - Perimal-Lewis, Lua; Bradley, Clare; Hakendorf, Paul; Whitehead, Craig; Heuzenroeder, Louise; Crotty, Maria
Abstract Background The discrepancy between the number of admissions and the allocation of hospital beds means that many patients admitted to hospital can be placed in units or wards other than that which specialise in the patient's primary health issue (home-ward). These patients are called 'outlier' patients. Risk factors and health system outcomes of hospital care for 'outlier' patients diagnosed with dementia and/or delirium are unknown. Therefore, the aim of this research was to examine patient journeys of people with dementia and/or delirium diagnoses, to identify risk factors for 'inlier' or 'outlier' status and patient or health system outcomes (consequences) of this status. Methods A retrospective, descriptive study compared patients who had dementia and/or delirium according to the proportion of time spent on the home ward i.e. 'inliers' or 'outliers'. Data from the patient journey database at Flinders Medical Centre (FMC), a public hospital in South Australia from 2007 and 2014 were extracted and analysed. The analysis was carried out on the patient journeys of people with a dementia and/or delirium diagnosis. Results When 6367 inpatient journeys with dementia and/or delirium within FMC were examined, the Emergency Department (ED) Length of Stay (LOS) after being admitted as inpatient was prolonged for 'outlier' patients compared to 'inlier' patients (OR: 1.068, 95% CI: 1.057–1.079, p  = 0.000). However, the inpatient LOS for'outlier' patients was only marginally shorter than that of the 'inlier' patients (OR: 0.998, 95% CI: 0.998–0.998, p  = 0.000). The chances of dying within 48 h of admission increased for 'outlier' patients (OR: 1.973, 95% CI: 1.158–3.359, p  = 0.012) and their Charlson co-morbidity Index was higher (OR: 1.059, 95% CI: 1.021–1.10, p  = 0.002). Completion of discharge summaries within 2 days post-discharge for 'outlier' patients was compromised (OR: 1.754, 95% CI: 1.492–2.061, p  = 0.000).Additionally, 'outlier' patients were more likely to be discharged to another hospital for other care types not offered at FMC (OR: 1.931, 95% CI: 1.559–2.391, p  = 0.000). Conclusion An examination of the patient journeys at FMC has determined that the health system outcomes for patients with dementia and/or delirium who are admitted outside of their home-ward are affected by in-hospital location despite the homogenous nature of the study population.